Biotin fortification to sperm preparation medium enhances the motility and longevity by reducing lipid peroxidation in cryopreserved sperm - Ranjan, Ravi; KUMAR, M; SINGH, S P; KHARCHE, S D; SINGH, M K; CHAUHAN, M S (The Indian Journal of Animal Sciences, 2022)
Biotin supplementation to the sperm cryopreservation medium appears to be beneficial in enhancing the in vitrosperm survival without affecting the fertilizing ability. Since, biotin is an essential micronutrient, it may be a safer sperm motility enhancing agent. We inferred that the fortification of 3 μM biotin significantly (P